Performance study on removal of NO in coal-fired flue gas via photothermal synergistic catalysis of H2O2 over copper-modified TiO2/carbon fiber film - Juan YANG; Chongchong LENG; Ge ZHANG; Qiyue SHAN; Zhixiang FENG (Meitan xuebao, 2024)
Flue gas emitted by coal-fired power plants contains a large amount of nitrogen oxides (NOx). Solar energy driven photocatalysis technology provides a novel approach of near-zero emission for flue gas denitrification, however the efficiency of single photocatalytic denitrification is limited. To achieve efficient removal of high concentration NO from coal flue gas, the development of a collaborative oxidation denitrification technology based on photocatalysis is urgently required. Defective TiO2 (D-TiO2) nanosheets with rich oxygen vacancies were first prepared by the hydrothermal method combined with H2 reduction treatment, and then CuOx was loaded onto D-TiO2 surface via the liquid phase impregnation approach to synthesize CuOx/D-TiO2 nanocomposites. Microscopic composition and energy-band structure of composite catalysts were determined by the transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), room temperature electron paramagnetic resonance (EPR) and UV-visible diffuse reflection spectroscopy. The results showed that the supported copper species was mixed valence CuOx, and the modification of CuOx did not affect the micro-morphology of D-TiO2, but enabled its conduction-band potential negative shift, consequently enhancing the reduction ability of photogenerated electrons. CuOx/D-TiO2 composites were served as the catalysts to activate H2O2, and the effect of CuOx loading amount on NO removal rate was studied under simulated solar light irradiation. By using the optimal 5% CuOx/D-TiO2 catalyst, the influences of simulated flue gas velocity and initial NO concentration on denitrification activity were investigated. DFT calculation results based on the density functional theory indicated that oxygen vacancies were conductive to NO adsorption and activation. Photoelectrochemical characterization and EPR test results displayed that incorporating CuOx not only promoted the charge separation efficiency of D-TiO2, and also played a crucial cocatalyst role as the active sites of H2O2 decomposition to produce ·OH. Radical quenching tests indicated that the surface ·OH was primary active radicals for NO photo-oxidative removal. The synergistic effect of cocatalyst CuOx and oxygen vacancies elevated the removal rate of NO from 15.1% of TiO2 to 63.8% of 5% CuOx/D-TiO2. Moreover, 5% CuOx/D-TiO2 was immobilized on the surface of modified carbon fiber (MCF) to construct monolithic catalyst CuOx/D-TiO2/MCF. The photothermal effect of MCF supporter can convert the absorbed near-infrared light into heat, producing local temperature rise on the surface of CuOx/D-TiO2. It dramatically accelerated photoelectrons interface transport and H2O2 decomposition reaction kinetics, further improving NO removal rate up to 95.2%. Additionally, the main product of NO photo-oxidative removal was \begin{document}${\rm{NO}}_3^ - $\end{document}, which can be used to produce nitrogen fertilizer. The detected byproduct NO2 was only 4.7 mg/m3. The concentration of NO2 and residual NO were much lower than the ultra-low emission standard of coal-fired boilers with NOx concentration of no more than 50 mg/m3. Durability test results showed that this monolithic catalyst CuOx/D-TiO2/MCF can purify high concentration of NO in flue gas under continuous operation conditions. The foregoing results demonstrate that the photothermal synergistic catalytic system based on CuOx/D-TiO2/MCF has a favorable application prospect in the field of industrial flue gas denitrification and nitrogen resource utilization.